Physicochemical and Textural Properties of Pomelo (Citrus maxima Merr. cv. Kao Nam Pueng) Fruit at Preharvest, Postharvest and During the Commercial Harvest Period - Sirisomboon, Panmanas (Philippine Agricultural Scientist, The (Formerly the Philippine Agriculturist), 2012)
We used the plate compression test and the puncture test to study the physicochemical and textural properties of pomelo (Citrus maxima Merr. cv. Kao Nam Pueng) from the end of cell enlargement to the mid-maturation period, which also included the commercial harvest period. The CIE lightness (L*) and CIE blue-yellow (b*) color coordinates of the peel increased over time, while CIE red-green (a*) decreased. Pomelo fruits at preharvest and during commercial harvest were of acceptable taste and quality with a soluble solids content (SSC) to acidity (A) ratio of 10:16. While firmness of the fruit decreased with maturity, the elasticity properties remained the same. The flavedo was tougher; lamella and flesh strength decreased; and albedo strength remained the same, indicating that the physiological structure of the albedo may not have changed during this stage. L* and b* were correlated with the strength of the lamella (RM), the penetrating force (PFF) and energy (PEF) in the flesh of pomelo. SSC/A was correlated with the weight of the fruit, L*, a*, b* of the peel, PFF and PEF, and as indicated by results of the non-destructive test, the flavor and flesh texture could be monitored during the maturation stage. SSC and A were correlated with RM, and A with PFF and PEF. The deformation ratio correlated well with average firmness (AF) of the fruit, which indicated that the ability of the fruit to perceive strain depended on the AF. This study is unique in demonstrating the change and correlation among the physicochemical and textural properties of pomelo during maturation.